A New Basic Ionic Liquid Supported on Magnetite Nanoparticles: An Efficient Phase-Transfer Catalyst for the Green Synthesis of 2-Amino-3-Cyano-4H-Pyrans. (28th May 2022) - Fallah-Mehrjardi, Mehdi; Shirzadi, Mahdieh; Banitaba, Sayed Hossein
Abstract: An efficient and straightforward procedure has been developed for the synthesis of 2-amino-3-cyano-4 H -pyrans via the one-pot three-component reaction of benzaldehydes, malononitrile and 1, 3-dicarbonyl compounds using a new nanomagnetite-supported organocatalyst (MNP@PEG-ImOH) in aqueous media. The MNPs are fully characterized by various techniques including Fourier transform infrared spectroscopy (FT-IR), field-emission scanning electron microscopy (FESEM), energy-dispersive X-ray (EDAX), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and vibrating sample magnetometry (VSM). The catalyst could readily be separated from the reaction mixture using an external magnet and could be reused in subsequent runs without a notable decrease of activity.